ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN AGROWISATA (STUDI KASUS DI STUDY WISATA BUKIT FLORA, DESA GUNUNG PETUNG, NONGKOJAJAR, KECAMATAN TUTUR, KABUPATEN PASURUAN) - Ahmad Yusuf Kholil; Farah Mutiara (Universitas Tribhuwana Tunggadewi, 2018)
The first purpose of the research were to identify and analyze potential of agrotourism Bukit Flora and potential area to support development agrotourism Bukit Flora. The second purpose is to identify and analize internal and external environment agrotourism Bukit Flora the factors into strengths, weaknesses, oppurtunities and threats for development agrotourism of Bukit Flora and the last purpose in this research is formulate appropriate strategies for development strategy of agrotourism Bukit Flora.Data analysis method use descriptive analysis and qualitative analysis. Descriptive analysis was used to analyze the potential of agrotourism Bukit Flora and identify the main factors to give weight to the factors that we have setconsisting of strengths, opportunities, weaknesses and threats by comparing the rows and columns of each variable on internal factors (IFE) and external (EFE). While the use of qualitative analysis in the form of a SWOT analysis and SWOT matrix IE matrix is used to analyze the development of agrotourism strategy using analysisQSPM.IFE total weighted scores of 2.56 and 2.30 for EFE. Placing agro Bukit Flora is in cell V. Based on the results of the SWOT matrix analysis, it can be obtained by four alternative strategies that can be taken in the development of agro Bukit Flora. Based on the results QSPM matrix, the value of the attraction was highest at 3 strategy with the total amount of the appeal (TAS) was 6.26.